2015
DOI: 10.1080/0886571x.2015.1004286
|View full text |Cite
|
Sign up to set email alerts
|

Effective Factors on Youth Satisfaction from Public Urban Spaces in Tehran

Abstract: The present research aims to study youth satisfaction from public urban environments and to identify the factors effective on youth satisfaction. The main question of the research is: What factors can affect youth satisfaction from public urban environments? This research has been performed by analytical-descriptive method. The statistical population consists of all youngsters in the age group of 13-17 years old in the city of Tehran, which was selected based on systematic random sampling method with a size of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Social cohesion Establish value, trust and collective norms, recover identity and the attempt to increase sense of place of residents to the township, preperation to use the urban priorities and deepening the urban culture for the informal inhabitants, social cohesion as a basis for collective identity Social security Define the human domain, observe private and public areas by the residents, getting rid of fear, risk and safety of any threat, tendnecy to be present in environemnt, increasing competence "Environmental quality has been used as an indicator used to measure the degree of environment that is appropriate for human life" [13]. Experts of different disciplines have done various researches in this area and especially on the quality of the residential environment in which two different approaches can generally be observed: 1-An independent concept that provides an overview of the quality of the components of an environment but it has more than its sum of effects on the overall perception of the place, 2) its definition of the more general concept of quality of life, which reflects all aspects of one's sense of well-being, including all the variables that affect human satisfaction [14].…”
Section: Social Participationmentioning
confidence: 99%
See 2 more Smart Citations
“…Social cohesion Establish value, trust and collective norms, recover identity and the attempt to increase sense of place of residents to the township, preperation to use the urban priorities and deepening the urban culture for the informal inhabitants, social cohesion as a basis for collective identity Social security Define the human domain, observe private and public areas by the residents, getting rid of fear, risk and safety of any threat, tendnecy to be present in environemnt, increasing competence "Environmental quality has been used as an indicator used to measure the degree of environment that is appropriate for human life" [13]. Experts of different disciplines have done various researches in this area and especially on the quality of the residential environment in which two different approaches can generally be observed: 1-An independent concept that provides an overview of the quality of the components of an environment but it has more than its sum of effects on the overall perception of the place, 2) its definition of the more general concept of quality of life, which reflects all aspects of one's sense of well-being, including all the variables that affect human satisfaction [14].…”
Section: Social Participationmentioning
confidence: 99%
“…Galster has defined this concept as the gap between residents' desires and needs and the current reality of their residential environment. [14].…”
Section: The Relationship Between Objective and Subjective Quality In Architecture With Residential Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Public spaces in cities, such as squares [10], parks [11], and residential areas [12], are our main research objects. The factors that affect satisfaction from public space [13][14][15] and the construction and quantification of an evaluation system [16,17] are the primary research contents. The Chinese government is currently investing heavily in renewing old residential areas to improve resident happiness [18].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of adequate urban services addressing children's needs is another reason for their absence in Iran's urban public spaces. Khodaee et al (2015) found that there was a relation between youth satisfaction and access to services, social security and the physical specifications of their dwelling places. A study in the city of Yazd found urban per capita spending in this city in comparison to the population of children, does not meet the needs of this group; for example, children do not have the proper play equipment (Shahrizadeh & Moayedfar, 2017).…”
Section: Introductionmentioning
confidence: 99%